(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the results of managing fetal distress during labor at Thai Binh Obstetrics and Gynecology Hospital in 2024 and identify some factors associated with the recorded results. Methods: A descriptive study was conducted through a prospective cross-sectional survey of the results of managing fetal distress during labor in 143 pregnant women diagnosed with fetal distress during labor at Thai Binh Obstetrics and Gynecology Hospital in 2024. Information was collected on maternal results, fetal results, 1-minute and 5-minute Apgar scores after birth, and some factors associated with the 1-minute Apgar score of the infant. Results: 100% of pregnant women had their babies delivered within 60 minutes of diagnosis, and 100% of mothers and babies were stable upon discharge. The obstetric complication rate was low (4.2%), including postpartum infection (2.1%) and postpartum hemorrhage (1.4%). 100% of the pregnancies were singletons, with an average weight of 3223.8 ± 306.0 grams. 93% of cases had an Apgar score of 8 at 1 minute; 99.3% had an Apgar score of 8 at 5 minutes. Factors associated with an increased risk of a low Apgar score at the first minute (< 8 points) included: frequent and strong uterine contractions (p < 0.05); abnormal fetal heart rate (p < 0.001); maternal obstetric complications (p < 0.005); and fetal bradycardia (< 120 beats/minute) (p < 0.001). Conclusion: The management of fetal distress at Thai Binh Obstetrics and Gynecology Hospital was highly effective, with 100% of cases receiving timely intervention within 60 minutes of detection, resulting in optimized Apgar scores and ensuring safety for both mother and child. Close monitoring of factors related to neonatal asphyxia (Apgar score < 8) plays a crucial role in predicting and improving the treatment outcomes of fetal distress in labor.